A new species of Pseudobagrus (Teleostei: Siluriformes: Bagridae) from southern China - Li, Jie; Chen, Xianglin; Chan, Bosco P.l. (Zootaxa, 2005)
A new species of bagrid catfish, Pseudobagrus gracilis, is described from specimens collected from the Zhujiang (Pearl River) basin, southern China. It closely resembles P. adiposalis Oshima and P. ussuriensis (Dybowski), but differs in having a large elliptical eye (19.8–24.4% HL), a short maxillary barbel not reaching the posterior margin of the eye, a lightly serrated posterior edge on the second dorsal spine, a caudal fin slightly emarginated with upper lobe slighter longer than lower lobe, frontal concave with a smooth surface, and supraoccipital process short (far from the first basal bone of the dorsal spine).